On the economics of audit partner tenure and rotation: Evidence from PCAOB data - Brandon Gipper; Luzi Hail; Christian Leuz (Goethe University Frankfurt, Center for Financial Studies (CFS), 2018)
We provide the first partner tenure and rotation analysis for a large cross-section of U.S. publicly listed firms over an extended period. We analyze the effects on audit quality as well as economic tradeoffs with respect to audit hours and fees. On average, we find no evidence for audit quality declines over the tenure cycle and, consistent with the former, little support for fresh-look benefits after five-year mandatory rotations. Nevertheless, partner rotations have significant economic consequences. We find increases in audit fees and decreases in audit hours over the tenure cycle, which differ by partner experience, client size, and competitiveness of the local audit market. Our findings are consistent with efforts by the audit firms to minimize disruptions and audit failures around mandatory rotations. We also analyze special circumstances, such as audit firm or audit team switches and early partner rotations. We show that these situations are more disruptive and more likely to exhibit audit quality effects. In particular, we find that lowquality audits give rise to early engagement partner rotations and in this sense have (career) consequences for partners.
Keywords: J01; J44; L84; M21; M42; 330; Auditing; Audit fees; Audit quality; Auditor rotation; Audit partner tenure; Competition; PCAOB